Climate variation is filtered differently among lakes to influence growth of juvenile sockeye salmon in an Alaskan watershed. Issue 6 (14th January 2014) - Griffiths, Jennifer R.; Schindler, Daniel E.; Ruggerone, Gregory T.; Bumgarner, Joseph D.
<x xml:space="preserve">Abstract</x> The physical landscape filters regional climate variation such that the environmental conditions an organism experiences are unique to the characteristics of local habitat features. While it has become apparent that populations may show watershed‐specific responses to changing climate within a geographic region, the population dynamics of Pacific salmon Oncorhynchus spp. suggest that within watershed climate filtering is also important. Growth provides an integrated measure of habitat quality capturing the overall response of individuals to climate as filtered by their habitat and their response to the biological interactions in the ecosystem. We used two different long‐term datasets, scales from returning adults and juvenile length measurements, to assess the response of sockeye salmon O. nerka growth during their juvenile life phase to single and integrated measures of climate within a watershed between 1950 and 2010. Scale growth showed evidence for differences among stocks rearing in different lake habitats within the same Alaska Peninsula watershed. These lakes have substantially different morphometry and showed opposite responses to changes in spring and fall air temperatures. Juvenile length data were also available for one of these stocks and indicated that density effects were relatively weak in contrast to the effects of temperature. While direct measures of juvenile length and measures derived from adult scales showed some similarity in their trends over time, they indicated opposite effects of air temperature. Throughout the range of Pacific salmon, climate change is altering freshwater ecosystems through changes to temperature, precipitation and associated variables. These data suggest that sockeye salmon populations are experiencing climate filtering at a sub‐watershed scale. Maintaining connected, heterogeneous landscapes will therefore likely be important for providing productive habitat for sockeye salmon across a range of climate conditions that they are going to experience under new climate regimes.